Knowledge about Nutrition and Testing Gestational Hypertension in Multiple Pregnancies - Wenang, Supriyatiningsih; Kurniawan, Muhammad; Rachmanio, Nicko (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Hypertensive disorders in pregnancy (HDP) are a leading contributor to maternal, fetal, and newborn death all over the world, including in Indonesia. Routine pregnancy check-ups and nutritional status can prevent pregnancy complications due to HDP.Objective: To increase health workers’ knowledge about the importance of blood pressure check-ups and adequate nutrition during multiple pregnancies.Methods: The PKM material was delivered through online seminars with 20 employees and their families at Asri Medical Center Hospital. The material provided included knowledge about women's health, multiple pregnancies, nutrition for pregnant women, as well as hypertension in pregnancy, and their management. Pretest and posttest was conducted. The analysis method used Wilcoxon Signed Rank test.Results: The analysis showed a 25% increase in knowledge from the results of the pretest of 75% to a total of 100% at the time of the posttest (p < 0.05), which suggests that there is a difference in the respondents’ knowledge levels about the importance of nutrition and examination of hypertension in multiple pregnancies.Conclusion: There is a significant difference in knowledge about the importance of nutrition and examination of hypertension in multiple pregnancies before and after the seminar at AMC Muhammadiyah Hospital.